2015
DOI: 10.1016/j.joca.2014.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronan molecular weight distribution is associated with the risk of knee osteoarthritis progression

Abstract: summary Objective We investigated the relationship between the molecular weight (MW) distribution of hyaluronan (HA) in synovial fluid (SF) and risk of knee osteoarthritis (OA) progression. Methods HA MW was analyzed for 65 baseline knee SFs. At 3-year follow-up, knees were scored for change in joint space narrowing (JSN), osteophyte (OST) progression, or occurrence of total knee arthroplasty (TKA). HA MW distribution was analyzed using agarose gel electrophoresis (AGE), and its relationship to OA progressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
67
1
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(85 citation statements)
references
References 29 publications
(32 reference statements)
5
67
1
5
Order By: Relevance
“…A number of prior studies have focused on the need to accurately place the needle intraarticularly and completely aspirate as much effusion as possible prior to injection, and all have generally demonstrated improved joint injection outcomes [5,18,27-29]. In 2003 Weitoft et al demonstrated that complete aspiration of the knee prior to corticosteroid injection prolonged the time-to-flare, and thus, reduced the need for repetitive corticosteroid injection [5].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of prior studies have focused on the need to accurately place the needle intraarticularly and completely aspirate as much effusion as possible prior to injection, and all have generally demonstrated improved joint injection outcomes [5,18,27-29]. In 2003 Weitoft et al demonstrated that complete aspiration of the knee prior to corticosteroid injection prolonged the time-to-flare, and thus, reduced the need for repetitive corticosteroid injection [5].…”
Section: Discussionmentioning
confidence: 99%
“…Extraction of joint fluid for biomarker analysis even in the dry (non-effusive) knee is presently an important area in arthritis research and may also be integral to future joint preservation strategies and therapies [6,22,29,30]. Similar to Bhavsar et al, Yaqub et al, and Meehan et al, but using a different study design, we found that mechanical compression permitted fluid extraction in a much greater proportion of osteoarthritic knees that presented clinically as dry, non-effusive knees (Figure 3) [7-9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of the existing OA-related biomarker assays have grown directly out of an understanding of joint tissue metabolism[8, 9] and reflect catabolism or anabolism of joint tissues. To the extent that many of the products of joint tissue metabolism can stimulate an innate immune response (for instance fibronectin and hyaluronan fragments)[10-13], and be detected in biospecimens[3, 14, 15], there is a potential to have some OA-related biomarkers that are directly involved in the pathophysiology of an OA disease outcome. This is an enviable scenario that has rarely been achieved in other disease areas but represents the holy grail of biomarker development.…”
Section: Introductionmentioning
confidence: 99%
“…Она входит и в состав синови-альной жидкости, определяя ее вязкоэластические свойства [9]. По мере прогрессирования ОА отмечается снижение молекулярной массы ГНК синовиальной жидкости, что мо-жет отрицательно повлиять на биомеханику сустава, хотя и не коррелирует с наличием артралгий [10].…”
unclassified